Perbedaan Hasil Pemeriksaan Kadar Glukosa Postprandial Yang Diberi Asupan Nasi Bungkus dan Roti Selai Srikaya - Hotman Sinaga; Feradisa Aditama; Rosnita Sebayang; Mustika Sari Hutabarat (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
According to the WHO in 2013, postprandial blood glucose examination and Oral Glucose Tolerance Test (TTGO) must use 75 grams of glucose dissolved in 250 ml. But in some laboratories when performing postprandial blood glucose test do not use 75 grams of glucose as recommended by WHO. Anyone use other substitutes such as package rice, which is complemented with side dishes, bread with srikaya jam, sweet tea, and bread with sweet tea. The type of study used is pre-experiment with Pretest and Posttest One Group. From a total subject 26 people. Subjects were asked to fast 10-12 hours, then blood was taken for fasting blood glucose levels. Subjects were divided into two groups, namely the group who received intake package rice and the group that received intake of srikaya jam bread. Subjects were asked to fast 2 hours. The average postprandial blood glucose level of packaged rice intake was 92.2 mg / dL while the average postprandial blood glucose level ofsrikaya jam bread intake was 91.5 mg / dL. No significant differences in the results of postprandial blood glucose level examination given the intake of packaged rice and srikaya bread with values (sig 2 tailed) 0.876> 0.025.